2018
DOI: 10.1186/s13058-018-1044-5
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survival predicted by TP53 mutation status differs markedly depending on treatment

Abstract: BackgroundPrevious studies on the role of TP53 mutation in breast cancer treatment response and survival are contradictory and inconclusive, limited by the use of different endpoints to determine clinical significance and by small sample sizes that prohibit stratification by treatment.MethodsWe utilized large datasets to examine overall survival according to TP53 mutation status in patients across multiple clinical features and treatments.ResultsConfirming other studies, we found that in all patients and in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 23 publications
3
64
0
Order By: Relevance
“…Breast cancers are frequently wild type for TP53 (Shahbandi and Jackson, 2019), and compelling evidence from our laboratory and others shows that chemotherapy-treated breast cancers that are TP53 wild type are more likely to have residual disease (Bertheau et al, 2002, 2007; Chen et al, 2012; Esserman et al, 2012; Nakamura et al, 2012; Wang et al, 2016; Goetz et al, 2017), with senescent cells present (te Poele et al, 2002; Jackson et al, 2012; Tonnessen-Murray et al, 2018), resulting in markedly worse survival (Ungerleider et al, 2018). The present study reveals a previously unknown ability of chemotherapy-induced senescent cancer cells to engulf and degrade nearby cells, resulting in enhanced survival and providing compelling explanations for well-known but poorly understood senescent cell phenotypes such as SASP and SA-βGAL staining.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Breast cancers are frequently wild type for TP53 (Shahbandi and Jackson, 2019), and compelling evidence from our laboratory and others shows that chemotherapy-treated breast cancers that are TP53 wild type are more likely to have residual disease (Bertheau et al, 2002, 2007; Chen et al, 2012; Esserman et al, 2012; Nakamura et al, 2012; Wang et al, 2016; Goetz et al, 2017), with senescent cells present (te Poele et al, 2002; Jackson et al, 2012; Tonnessen-Murray et al, 2018), resulting in markedly worse survival (Ungerleider et al, 2018). The present study reveals a previously unknown ability of chemotherapy-induced senescent cancer cells to engulf and degrade nearby cells, resulting in enhanced survival and providing compelling explanations for well-known but poorly understood senescent cell phenotypes such as SASP and SA-βGAL staining.…”
Section: Discussionmentioning
confidence: 97%
“…Engulfment by senescent cells increased their survival and could provide building blocks that might enable SASP to drive relapse. These factors suggest immediate clinical relevance, as p53-mediated induction of senescence contributes to poor response (Bertheau et al, 2002; Jackson et al, 2012) and poor survival (Ungerleider et al, 2018) of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Luminal B and Her2 + subtypes generally have lower overall survival owing to their fast growth and tendency to relapse after removal. Likewise, basal-like breast cancer is associated with poor overall survival, partly due to increased metastatic potential and a lack of targeted therapeutic strategies 22,34,35 , although a proportion of these patients are associated with good prognosis 36 . These observations led us to ask whether Gas6 expression in human breast cancers correlates with overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The association between overexpression of p53 and poor prognosis has been reported in premenopausal breast cancer patients treated with tamoxifen after chemotherapy (16). A recent study has also demonstrated that TP53 wild-type status conferred superior 5-year overall survival in patients treated with adjuvant endocrine therapy (17). We previously reported that 20% of ER-positive breast cancer patients showed p53 accumulation by IHC (18), and that p53 accumulation predicted resistance to endocrine therapy and decreased post-relapse survival in metastatic breast cancer (19).…”
mentioning
confidence: 87%